RELATIONSHIP BETWEEN EXERCISE AND ANDROGENIC ALOPECIA - Frida Angelina; Clorinda Chandra; Indira Vidiari Juhanna; I Putu Adiartha Griadhi (Sport and Fitness Journal, 2023)
Androgenic alopecia is a common cause of thinning hair whose prevalence increases with age and aging. The incidence of alopecia is also related to genetic and non-genetic factors, including exercise, although research is still limited. Therefore, this literature review was organized to examine the relationship between androgenic alopecia and exercise in more detail. An article search was conducted in five electronic journal databases (Google Scholar, PubMed, ScienceDirect, MEDLINE, and EMBASE) to find scientific articles on the relationship between exercise and androgenic alopecia published within the last ten years (2013-2023), without language restrictions, with criteria inclusion as follows: 1) respondents with androgenic alopecia; 2) an explanation of the relationship between exercise and androgenic alopecia; and 3) description of the effect of intensity, frequency, and form of exercise on the incidence of androgenic alopecia. In total, there were two cross-sectional studies used in this literature review. This study found that an increase in the frequency of low-intensity exercise in the group with or without a family history of androgenic alopecia increased the proportion. However, progressivity can be reduced, and symptom improvement can occur in the group that does any exercise lasting more than 60 minutes with a frequency of 5-7 times per week, so this exercise method can be recommended. Thus, this literature review has answered that there is a relationship between exercise and the incidence of androgenic alopecia, which can increase or decrease the progression and symptoms depending on the type, intensity, duration, and frequency of exercise. Keywords: aging; androgenic alopecia; exercise; progressivity